Comparison of respiratory functions of university level male ball game players / Amandeep Singh - Singh, Amandeep (Faculty of Sports Science and Recreation, 2015)
The purpose of this study was to compare the respiratory parameters among university level ball game players. A sample of Ninety (N = 90) male ball game players (mean ± SD: age 20.65 ± 1.44 years, height 179.10 ± 7.72 m, weight 69.29 ± 9.38 kg, BMI 21.57 ± 9.36), which includes thirty each volleyball, basketball and football players, who participated in inter – college competitions of Guru Nanak Dev University, Amritsar, India, was selected. All the participants were informed about aim and methodology of the study and they volunteered to participate in this study. The study was conducted on selected respiratory functions i.e. vital capacity, expiratory reserve volume, inspiratory reserve volume, inspiratory capacity and forced vital capacity. One way Analysis of Variance (ANOVA) was applied to find out the significance of differences with regard to selected respiratory functions among elite ball game i.e. volleyball, basketball and football players. Scheffe’s post-hoc test (SPHT) was applied to see the direction and significance of differences where ‘F’ value found statistically significant. The level of significance was set at 0.05. While comparing the means, it revealed that basketball players had better vital capacity, expiratory reserve volume, inspiratory reserve volume, inspiratory capacity and forced vital capacity than their counterparts; football and volleyball players. Further, significant differences were found between different male ball game i.e. football, basketball & volleyball players with regard to vital capacity (p˂ 0.05), expiratory reserve volume (p˂ 0.05), inspiratory reserve volume (p˂ 0.05), inspiratory capacity (p˂ 0.05) and forced vital capacity (p˂ 0.05) respectively.